Detection of IgA Antiphospholipid Antibodies Does not Improve Thrombotic Antiphospholipid Syndrome Classification: A two-Center Study - Su, Zhenzhen; Huang, Zhuochun; Zhao, Jiuliang; Li, Mengtao; Hu, Jing; Zeng, Xiaofeng; Hu, Chaojun; Yang, Bin (Clinical and applied thrombosis/hemostasis, 2022)
Background Thrombotic antiphospholipid syndrome (APS) is a systemic autoimmune disease; its diagnosis requires meeting both clinical and laboratory criteria. Prevalence rates of immunoglobulin (Ig) A anticardiolipin antibodies (aCL) and IgA anti-β2 glycoprotein I antibodies (aβ2GPI) remain unknown, and the clinical value of these antibodies to APS classification remains controversial. Therefore, we aimed to examine both items in the Chinese population. Methods Using chemiluminescence immunoassay, antiphospholipid antibodies (aPL) were quantified in 12,582 hospital-based general population, 278 thrombotic APS patients, and 233 healthy controls. Results In the general population, the positive rates of IgA aCL and IgA aβ2GPI antibodies were 2.87% and 1.99%, respectively. Furthermore, isolated IgA aPL-positivity rate was 0.72% in patients with APS, which was comparable to those in the general population (0.68%, p = 1) and in healthy controls (0.43%, p = 1). Among the IgA aPL-positive individuals in the general population, isolated IgA-positive individuals had lower serum levels of IgA antibodies (p = 0.007 for IgA aCL and p = 0.059 for IgA aβ2GPI). Regarding to APS classification, adding IgA aPL into conventional aPL assays may not improve and may even deteriorate the net reclassification index for APS; besides, no association between thrombosis and IgA aPL was observed. Conclusions this study assessed the prevalence of various aPL in Chinese population. IgA aPL may not enhance the classification ability of established laboratory criteria for thrombotic APS. Our data do not support the addition of IgA aPL to conventional aPL assays.